Intravenous Transplantation of Human Hair Follicle-Derived Mesenchymal Stem Cells Ameliorates Trabecular Bone Loss in Osteoporotic Mice - Lin, Longshuai; He, Enjun; Wang, Hongjie; Guo, Weihong; Wu, Zhenkai; Huang, Kai; Zhao, Qinghua (Frontiers in Cell and Developmental Biology, 2022)
Background: Hair follicles harbor a rich autologous stem cell pool and human hair follicle-derived mesenchymal stem cells (hHF-MSCs) have multi-lineage differentiation potential. Many sources of MSCs include hHF-MSCs have been attractive candidates for cell therapy, regenerative medicine and tissue engineering. The present study is to explore the effect of intravenous transplantation of hHF-MSCs on bone mass in osteoporotic mice and its mechanism, and provides prospects for clinical applications for the treatment of osteoporosis with hHF-MSCs. Methods: Physically pull out about 20 hairs with intact hair follicles from the occipital area of the scalp of healthy volunteers, and separate and extract hair follicle-derived fibroblast-like cells. In vitro culture and characterization of these cells. Intravenous injection of hHF-MSCs was performed on ovariectomy-induced and age-related osteoporotic SCID mice for osteoporosis treatment. The mice were sacrificed 7 weeks after the second injection and samples were collected. The long bones and L1 vertebrae were collected for micro-CT scan, histomorphometry and immunohistochemical analysis. Peripheral serum were collected for ELISA analysis and antibody array. Results: These hair follicle-derived fibroblast-like cells have surface markers of MSCs, tri-lineage differentiation potentials toward adipocytes, chondrocytes, and osteoblasts, and immunomodulatory effects, were defined as hHF-MSCs. Intravenous transplantation of hHF-MSCs can better restores trabecular bone mass in osteoporotic mice. The double calcein labeling assay, trap staining of bones and ELISA analysis of bone formation and resorption markers in peripheral serum showed that after hHF-MSC transplantation, bone formation was enhanced and bone resorption was weakened. Antibody array and immunohistochemical analysis showed that several cytokines including OPG, RANKL, Noggin, VCAM-1, and Wnt2b might be involved in this process. Conclusions: Human HF-MSCs transplantation can combat trabecular bone loss induced by menopause and aging in mice. And the above mechanism that hHF-MSCs transplantation inhibits bone resorption and promote bone formation is related to OPG, VCAM-1, RANKL, Noggin and Wnt2b.